2021
DOI: 10.1111/nph.17595
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome‐mediated effects of habitat fragmentation on native plant performance

Abstract: Habitat fragmentation is a leading cause of biodiversity and ecosystem function loss in the Anthropocene. Despite the importance of plant-microbiome interactions to ecosystem productivity, we have limited knowledge of how fragmentation affects microbiomes and even less knowledge of its consequences for microbial interactions with plants.Combining field surveys, microbiome sequencing, manipulative experiments, and random forest models, we investigated fragmentation legacy effects on soil microbiomes in imperile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 100 publications
(147 reference statements)
2
24
1
Order By: Relevance
“…Soil microbiome biodiversity as measured by eDNA reveals a complex community composition. Microbiome families respond to habitat, with the habitat comprising the physical and biotic factors that support the species' survival and reproduction (Kiesewetter and Afkhami, 2021;Wang et al, 2022;Keet et al, 2019). By considering the co-occurring eDNA and image spectroscopy data, our results demonstrate that ecosystem functions and hence related processes such as the presence and relative abundance of microbiome families, can be deductively interpreted, also in ecosystems with vegetation cover.…”
Section: Discussionmentioning
confidence: 87%
“…Soil microbiome biodiversity as measured by eDNA reveals a complex community composition. Microbiome families respond to habitat, with the habitat comprising the physical and biotic factors that support the species' survival and reproduction (Kiesewetter and Afkhami, 2021;Wang et al, 2022;Keet et al, 2019). By considering the co-occurring eDNA and image spectroscopy data, our results demonstrate that ecosystem functions and hence related processes such as the presence and relative abundance of microbiome families, can be deductively interpreted, also in ecosystems with vegetation cover.…”
Section: Discussionmentioning
confidence: 87%
“…Evaluating how complex community shifts directly relate to changes in plant performance is an important avenue for future research. Being able to recruit native soil microbial assemblages appears critical to reconnecting above‐belowground processes, as it has been shown that native microbes are critical for native plant emergence and establishment (Moreira‐Grez et al 2019; Kiesewetter & Afkhami 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These secondary chemicals could potentially mediate whether mutualist partners meet and travel together, and their absence in models involving the co-movement of mutualists could lead to erroneous results. Kasey Kiesewetter's presentation, Fragmentation-driven effects on beneficial microbiomes drive changes in native plant performance, focused on how habitat fragmentation and urbanization impact soil microbial communities and how this affects the plants they associate with (Kiesewetter and Afkhami 2021). They collected soil samples from undisturbed and urban locations with varying levels of fragmentation in Florida's Pine Rockland ecosystem.…”
Section: Article E2063mentioning
confidence: 99%